Best practices recommendations for estimating dissipation rates from shear probes - Lueck, Rolf; Fer, Ilker; Bluteau, Cynthia; Dengler, Marcus; Holtermann, Peter; Inoue, Ryuichiro; LeBoyer, Arnaud; Nicholson, Sarah-Anne; Schulz, Kirstin; Stevens, Craig (Frontiers in Marine Science, 2024)
As a part of the Scientific Committee on Oceanographic Research (SCOR) Working Group #160 “Analyzing ocean turbulence observations to quantify mixing” (ATOMIX), we have developed recommendations on best practices for estimating the rate of dissipation of kinetic energy, ε, from measurements of turbulence shear using shear probes. The recommendations provided here are platform-independent and cover the conceivable range of dissipation rates in the ocean, seas, and other natural waters. They are applicable to commonly deployed platforms that include vertical profilers, fixed and moored instruments, towed profilers, submarines, self-propelled ocean gliders, and other autonomous underwater vehicles. The procedure for preparing the shear data for spectral estimation is discussed in detail, as are the quality control metrics that should accompany each estimate of ε. The methods are illustrated using a high-quality ‘benchmark’ dataset, while potential pitfalls are demonstrated with a second dataset containing common faults.